Dumézil revurderet - Bjerring-Nielsen, Bent (Religionsvidenskabeligt Tidsskrift, 2003)
This article is a discussion of George Dumézil’s theory of a unique Indo-European ideology characterised by the tendency to think in three basic functions. Based on an earlier attempt by John Brough to critizise the theory on this point, the article presents an analysis of the ‘First Kings of Israel’ in the Hebrew Bible that shows their expression of the three-functionel ideology. This leads to the conclusion that while Dumézil has managed to show that the three-functional ideology is a typical Indo-European trait, it cannot be regarded as uniquely Indo-European.